Creación de un centro de acopio para la comercialización de plantas ornamentales que mejoren los ingresos de los productores del recinto Linderos de Venecia del cantón Milagro - Villalta Vizñay, Jenny Janeth (2015)
In currently on site Linderos de Venecia, located at kilometer 5 ½ on the road to Naranjito, belonging to Cantón Milagro, have entered a large number of intermediaries because they carry the primary sector, which is represented mostly the activity of planting and propagation of ornamental plants with the widest range of varieties of the sector which has been a source of income for many years given by qualities of the land and climate that are very suitable for growing ornamentals plants. Due to the advantages of climate and soil are very productive in nurseries a variety of plants sown, reaching different sizes and colors very showy and embellish any environment, and that today are used in the decoration of houses, neighborhoods, avenues, parks and different tourist attractions around the country……..